Russia, Oriente slavo e Occidente europeo. Fratture e integrazioni nella storia e nella civiltà letteraria Fratture e integrazioni nella storia e nella civiltà letteraria - ne Priadko (Biblioteca di Studi Slavistici, 2017)
The present book faces a wide range of problems concerning the history of Eastern slavic culture in its interation with cultural models, typical of Western Europe. This collective work is the final result of the french-italian congress "Fractures and Integrations between Russia, East Slavic world and the West. History and literary civilisation from the Middle Age to the Contemporary Era" (University of Florence, 16-17 april 2015): the complexity of cultural relations between Russia, Slavic East and European West is analysed enhancing the variety of points of view and benefiting of different methodological approaches as well as from perspectives, provided from different fields of study. Here we introduce new materials and new analytical methods, which are useful for studying the complex interactions between the western cultural tradition and the east oriental one, from Middle Age up to nowadays. The "fractures" and "integrations" are therefore highlighted throughout the reading or critical re-reading of textes, works and authors, who took part to the construction and the development of cultural interchange among the various european areas.